Poster Media Use in Arabic Reading Instruction at Junior High School: Penggunaan Media Poster dalam Pengajaran Membaca Bahasa Arab di Sekolah Menengah Pertama - Widya Sahda Tiffany Ardiningrum; Eni Fariyatul Fahyuni (Universitas Muhammadiyah Sidoarjo, 2025)
General Background Arabic language instruction at the junior high school level requires learning media that support students’ comprehension skills, particularly in reading Arabic texts. Specific Background In the observed context, Arabic reading instruction was largely conducted using conventional materials such as textbooks and the blackboard, which limited student engagement and comprehension during maharah qiraah learning activities. Knowledge Gap There remains limited empirical documentation on the application of visual graphic media, specifically posters, in supporting Arabic reading instruction at the junior high school level in Indonesian classroom settings. Aims This study aims to examine the use of poster media in maharah qiraah learning for junior high school students in Sidoarjo. Results The findings indicate a significant difference between students’ reading performance before and after the use of poster media, demonstrating measurable learning gains in maharah qiraah activities. Novelty This study presents structured evidence of poster media application as a visual learning resource in Arabic reading instruction at the junior high school level. Implications The results suggest that poster-based learning media can be considered as an alternative instructional resource to support Arabic reading instruction and diversify classroom learning practices. Highlights Visual graphic materials supported student reading performance in Arabic learning activities. Learning outcomes differed between pre-learning and post-learning conditions. Classroom instruction benefited from diversified instructional resources beyond textbooks and boards. Keywords: Poster Media, Arabic Language Learning, Maharah Qiraah, Junior High School, Visual Learning Media